2022
DOI: 10.1111/mec.16636
|View full text |Cite
|
Sign up to set email alerts
|

Variable hybridization between two Lake Tanganyikan cichlid species in recent secondary contact

Abstract: Closely related taxa frequently exist in sympatry before the evolution of robust reproductive barriers, which can lead to substantial gene flow. Post‐divergence gene flow can promote several disparate trajectories of divergence ranging from the erosion of distinctiveness and eventual collapse of the taxa to the strengthening of reproductive isolation. Among many relevant factors, understanding the demographic history of divergence (e.g. divergence time and extent of historical gene flow) can be particularly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…Secondary contact provides the ultimate test of whether incipient species have diverged sufficiently to remain distinct. Population genomic analyses have revealed that introgression is quite common for taxa in secondary contact [1][2][3][4] and that introgression varies among contact zones [5][6][7] and parts of genomes 1 . However, the ecological factors and phenotypic traits that modulate the direction and magnitude of admixture, and its effects on species boundaries, remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary contact provides the ultimate test of whether incipient species have diverged sufficiently to remain distinct. Population genomic analyses have revealed that introgression is quite common for taxa in secondary contact [1][2][3][4] and that introgression varies among contact zones [5][6][7] and parts of genomes 1 . However, the ecological factors and phenotypic traits that modulate the direction and magnitude of admixture, and its effects on species boundaries, remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in introgression among independent contact zones may be caused by multiple mechanisms, e.g., differences in relative abundance 6 , the local genetic architecture of reproductive isolation, or the environmental context 7 . The environment can mediate both the expression of traits impacting hybridization 8,9 and the fitness consequences of hybridization and introgression 10 , making reproductive isolation context dependent.…”
Section: Introductionmentioning
confidence: 99%